2006
DOI: 10.1677/joe.1.06799
|View full text |Cite
|
Sign up to set email alerts
|

UbcH7 interacts with the glucocorticoid receptor and mediates receptor autoregulation

Abstract: Unlike other nuclear receptors, transactivation by the glucocorticoid receptor (GR) is increased by the inhibition of the ubiquitin/proteasome pathway. Here, we demonstrate that the ubiquitin-conjugating enzyme (E2), UbcH7, physically interacts with the GR and, when overexpressed, reduces the ability of the receptor to upregulate gene expression. Chemical inhibition of the 26S proteasome abolished the downregulation effect of overexpressed UbcH7, suggesting a role for the 26S proteasome, and GR protein stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…However, our finding is consistent with the observation that several nuclear receptors including GR are ubiquitinated and degraded in the course of their nuclear activities [21][22][23][24][25][26]. In addition to receptors, studies have revealed that coactivators, including steroid receptor coactivator 1 (SRC1), SRC2, SRC3, CBP and E6-associated protein (E6-AP), could also be ubiquitinated and degraded, through the proteosome, in order to disassemble and reassemble coactivator complexes, thereby promoting enhanced transcription [27].…”
Section: Bag-1m Is Not Involved In the Degradation Of Grsupporting
confidence: 92%
“…However, our finding is consistent with the observation that several nuclear receptors including GR are ubiquitinated and degraded in the course of their nuclear activities [21][22][23][24][25][26]. In addition to receptors, studies have revealed that coactivators, including steroid receptor coactivator 1 (SRC1), SRC2, SRC3, CBP and E6-associated protein (E6-AP), could also be ubiquitinated and degraded, through the proteosome, in order to disassemble and reassemble coactivator complexes, thereby promoting enhanced transcription [27].…”
Section: Bag-1m Is Not Involved In the Degradation Of Grsupporting
confidence: 92%
“…25 Inhibition of GR binding to target gene promoters by antagonists or GR mutation has been shown to abolish transactivation. 35,36 We found that OGD induced significant downregulation of the GR in our cEND in vitro system as did tMCAO in murine brains in vivo. Lack of functional GR prevented transcriptional modulation by GC thereby reversing genomic GC effects such as induction of TJ protein target genes leading to elevation of TER.…”
Section: Kleinschnitz Et Almentioning
confidence: 59%
“…To explore the molecular mechanism underlying potentiation of the GR by CoCl 2 , we measured the expression levels of the GR over time. Measurements were made upon Dex addition since several steroid hormone receptors like ERs or AR are destabilized by ligand binding (Dennis & O'Malley 2005; Garside et al . 2006; Ohtake et al .…”
Section: Resultsmentioning
confidence: 99%